Tafsir Wewenang Seponering Jaksa Agung Pasca Putusan Mahkamah Konstitusi Nomor 29/PUU-XIV/2016 - Ilham Dwi Rafiqi (Widya Yuridika, 2021)
The affirmation of the attorney general's authority in the Elucidation of Article 35 letter C of the Indonesian Prosecutor's Law after the decision of the Constitutional Court Number 29/PUU-XIV/2016 still leaves problems and has the potential to cause new legal problems. This research will look at and analyze how the authority of the Attorney General after the decision is as well as how the concept of an ideal arrangement that ensures legal certainty. This research uses normative juridical research with a statutory approach and case studies which in this case are court decisions. The results showed that after Constitutional Court decision, there was a change in the meaning of the Elucidation of Article 35 letter c of the Republic of Indonesia Prosecutor's Law. Based on the results of these interpretations and decisions, the legal implications that followed were related to the conditions for setting aside cases in the public interest, namely in setting aside cases in the public interest, the Attorney General was required to 'require' first to pay attention to suggestions and opinions from state power agencies that have relationship with the problem. The concept of an ideal arrangement that can guarantee legal certainty as an indicator to measure and assess the implementation of the Attorney General's obligations can be done by clarifying the definition of "state power agencies" for which advice and opinions are requested and making criteria for the term "public interest".